ANALISIS PENDEKATAN KONSEP SUSTAINABILITY DALAM JOB SHOP SCHEDULING SISTEM MANUFAKTUR - Febrianti, Risti; Darmawan, Bambang; Dwiyanti, Vina (Relawan Jurnal Indonesia, 2024)
Competition among manufacturing companies drives industrial growth to adopt a competitive pattern. One way for companies to compete and avoid falling behind is by optimizing production activities through scheduling each workstation (job shop scheduling). This scientific article employs a literature review method with an evidence-based approach to identify relevant case studies. The research findings indicate that the job shop scheduling model has a significant positive impact on companies, such as increasing production efficiency and enhancing resource performance, ultimately minimizing costs and production time. However, it cannot be overlooked that this model also has negative effects, such as increased waste, pollution, and depletion of non-renewable resources. Therefore, the manufacturing industry must implement the concept of sustainability, focusing on three main pillars: economic, environmental, and social aspects. This approach aims to maintain productivity, enhance the quality of production performance, and minimize risks associated with optimizing job shop scheduling, ensuring maximum profitability for the company.